Earth observation as enabler for implementing the EU regulation on deforestation-free products - Katja Berger; Martin Herold; Zoltan Szantoi (npj Climate Action)
Earth observation (EO) data are critical for transparent EUDR monitoring and reporting, serving as a key tool for compliance verification and climate change mitigation. We discuss how current and upcoming EO missions serve different stakeholder needs for independent, verifiable, global and long-term evidence of land use and commodities following deforestation and propose mandating EO data and tools for efficiently assessing environmental impacts.